Digital design and virtual simulation of sports bras based on TG3D-Nuno knitted fabric simulation - Liushan Tao; Anhua Zhong (PLoS ONE, 2026)
In response to the key issues in the current digital design of sports underwear, such as fabric simulation distortion, disconnection between dynamic and static verification, and lagging functional evaluation, this study proposes a full-process digital development method for rib-knitted sports underwear based on the collaboration of TG3D-Nuno and CLO3D. Taking cotton/spandex (78%/22%) rib-knitted fabric as the research object, its multi-dimensional physical properties such as color, normal, roughness, and displacement are collected through the TG3D-Nuno 3D scanning system. After parameter mapping and calibration, the high-fidelity reproduction of the fabric’s visual texture and mechanical properties is achieved in the CLO3D virtual environment. Moreover, combined with a standard female human model (height 175.3 cm, bust 80.6 cm), the pattern of a functional sports underwear integrating a front-opening zipper, crossed shoulder strap structure, and elastic hem is designed using the “3D pen” tool. Furthermore, by constructing a dynamic simulation scenario in a running posture, a systematic verification of the underwear’s fit, support stability, and fabric collaborative deformation characteristics during exercise is carried out. The experimental results show that the digital process established in this study significantly improves the virtual restoration accuracy of knitted fabrics. Based on the evaluation of the size matching degree index, the 3D matching degree of the optimized pattern in key areas exceeds 98%. The dynamic simulation effectively identifies and corrects functional defects such as shoulder strap slippage and insufficient cup fit. This method realizes a complete technical closed-loop from fabric digitization to dynamic function verification, providing a feasible technical solution for the rapid development and precise design of sports underwear.